Complications among Mothers and New Born Due to Delivery Process in Selected Hospitals of Rupandehi District Nepal - Sharma, Shanta; Dhakal, Indra (Journal of Nepal Health Research Council, 2018)
Background: Child birth is a universally celebrated occasion, yet everyday for thousands of women child birth is experienced not as a joyful event as it should be, but as a private hell that may even end in death. The objective of this study is to determine the complications of normal delivery and cesarean section on the mothers and new born.Methods: A descriptive study was conducted in two selected hospitals of Rupandehi district, Nepal. Data was collected as per pretested structured proforma from 550 respondents who were the mothers and new born delivered normally and through cesarean section randomly till the completion of sample size and analyzed by using SPSS, MANOVA and Chi-square test to determine associations between categorical variables.Results: In a total of 550 deliveries,25.8% were cesarean delivery, 42.7% motherssuffered from delivery related complications, common were PPH (21.1%), prolonged labour (8.5%) and wound infection (7.6%). 35.5% of newborn had complications, common were respiratory distress (6.3%) and neonatal jaundice (4.2%).Conclusions: Delivery related complications were higher among Lower segment cesarean section compared to vaginal delivery in mothers and newborn.